Blood culture positive sepsis and sensitivity pattern in NICU at a tertiary care neonatal centre - Singhvi, Manila; Singh, Poonam (International Journal of Contemporary Pediatrics, 2025)
Background: This study aims to study blood culture positive neonatal sepsis and the sensitivity pattern of pathogenic organisms in a tertiary neonatal care hospital. Methods: This retrospective observational cohort study was done in a tertiary care hospital. All the blood culture positive neonatal sepsis cases, excluding neonates with multiple congenital malformations, diagnosed during March 2023 to August 2023 (6 months) were analyzed. Results: A total of 73 neonatal sepsis cases were diagnosed, among them 40 (54.7%) cases of gram-positive sepsis. In present study 61.6% cases were early onset sepsis, 41 (56%) babies were preterm and 49 (67%) babies were inborn. Staphylococcus aureus and Acinetobacter were the most common organisms in early onset and late onset sepsis respectively. The sensitivity of Gram-negative bacilli to colistin, minocycline and levofloxacin was 90%, 84% and 78% respectively. The sensitivity of gram-positive organisms to linezolid, vancomycin and teicoplanin were 92%, 73% and 70% respectively. Mortality rate among culture positive sepsis was 16.4%. Conclusions: In the practice of modern neonatal care, multidrug organisms are emerging. By practicing antibiotic stewardship, infants can be protected from future multidrug resistance organisms.